2014
DOI: 10.1186/1746-4269-10-82
|View full text |Cite
|
Sign up to set email alerts
|

Effects of socio-economic household characteristics on traditional knowledge and usage of wild yams and medicinal plants in the Mahafaly region of south-western Madagascar

Abstract: BackgroundRural households in the Mahafaly region of semi-arid SW-Madagascar strongly depend on the exploitation of natural resources for their basic needs and income regeneration. An overuse of such resources threatens the natural environment and people’s livelihood. Our study focuses on the diversity and use of wild yams and medicinal plants.MethodsWe hypothesized that knowledge on the use of these resources highly depends on farmers’ socio-economic household characteristics. To test this hypothesis, an ethn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 42 publications
5
41
0
Order By: Relevance
“…Instead, the collection of medicinal plants and building material were positively associated with wealth. Andriamparany et al (2014) found that yam collection (one important kind of alimentary plants) is more frequent among poorer households in the same study region, while the collection of medicinal plants is related to cultural attitudes.…”
Section: Discussionmentioning
confidence: 82%
“…Instead, the collection of medicinal plants and building material were positively associated with wealth. Andriamparany et al (2014) found that yam collection (one important kind of alimentary plants) is more frequent among poorer households in the same study region, while the collection of medicinal plants is related to cultural attitudes.…”
Section: Discussionmentioning
confidence: 82%
“…Different types are identified by local people who prize their sweet taste, size of tubers, and claimed nutritional value. Wild yams have a central role in local food security in the Mahafaly region, especially for poor farmers (Andriamparany et al 2014).…”
Section: Culturally Significant Wild Edible Plantsmentioning
confidence: 99%
“…Charcoal production is less intensive on the plateau compared to the littoral, which is probably the result of environmental education efforts from NGOs in this region. Furthermore, the proportion of medicinal use is lower in the plateau compared to the littoral, mainly because of the availability of much more medicinal plants in the plateau, whereas inhabitants of the coastal area depend to a higher degree on tamarind products for medicinal purposes (Andriamparany et al, 2014).…”
Section: Importance Of Tamarindmentioning
confidence: 99%